Factors That Influence Consumer Attractiveness in Purchasing on Consumer Satisfaction Star Mobil Showroom - Valevy, Reza; Pristiyono, Pristiyono; Al Ihsan, Muhammad Ali (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The aim of this research is to prove that product innovation, price, and product quality influence the decision to purchase used cars in Labuhanbatu Regency. Data collection techniques include observation, questionnaires, literature studies, and documentation. The number of samples used in research using Partial Least Square-SEM analysis in this research was 50 consumers. This research uses descriptive statistical data analysis and Partial Least Square-SEM, which is an analysis used to develop or predict an existing theory. This research uses PLS structural model analysis with the help of SmartPLS 4.0 software. Structural model analysis has several stages, namely: 1) Formulating structural model theory, 2) Outer model analysis, 3) Inner model analysis, and 4) Hypothesis testing. The conclusion that can be conveyed in this research is that the hypothesized variables of product innovation and brand image partially influence the decision to purchase a used car. Meanwhile, the price variable does not have a strong relationship with the decision to purchase a used car. Finally, the purchasing decision variable influences consumer satisfaction in buying a used car, influenced by three indicators, namely product trust, other people’s views, and the presence of friends about the Star Mobil Rantauprapat showroom.